Conditions of Substrate and Water Quality Supporting Activites as A Growth Factor in Mangrove at Coastal Basaan I, South East District Minahasa - Adnan S. Wantasen (Sam Ratulangi University, 2013)
Mangrove forest vegetation contained in Basaan The village has an important role, both ecologically and economically for the community. The mangrove ecosystem's ability to maintain its ecological function depends on factors - environmental contributing factors, namely the quality of the environment and substrate conditions. The purpose of the study was to measure the quality of environmental factors and substrate waters around mangrove and describe the environmental capacity of water at mangrove ecosystem. The method of research by sampling at two locations: station A and station B by taking water samples in which the chemical and physical parameters of the test carried out in the Laboratory of Water archipelago and substrate samples which were tested in Laborarotium Soil Fertility, Faculty of Agriculture Unsrat Manado. The test results showed that the water temperature is 310C and TSS levels <1 (station A) and 44 (station B), pH 7.3; salinity 32; NH3 0.26 (A), 0.05 (B); PO4 0.122 (A ), 0.013 (B); H2S < 0.02; DO 10.10 (A), 8.95 (B). For the test results is the basic substrate pH H2O 7.6 (station A) and 7.5 (station B) neutral category; pH KCl 5.1 (A) and 5.4 (B) neutral category, N 0.44 (A ), 0.34 (B) medium category; P2O5 1.98 (A) and 15.35 (B) medium category; organic C-5.83 (A) and 3.98 (B) high category; K2O 2, 27 (A) and 23.48 (B) medium category. Conditions coastal waters village Basaan I still quite good because of the support and the dukungya still need attention orthoposphat parameter whose value is higher than the standard. Â Keywords : water quality, substrate base, carrying capacity